Assessing depressive symptoms among people living with HIV in Yangon city, Myanmar: Does being a member of self-help group matter? - Myat Wint Than; Nicholus Tint Zaw; Kyi Minn; Yu Mon Saw; Junko Kiriya; Masamine Jimba; Hla Hla Win; Akira Shibanuma (PLoS ONE)
Background While self-help groups have been formed among people living with HIV, few studies have been conducted to assess the role of self-help groups in mitigating depressive symptoms. This study investigated the association between self-help group membership and depressive symptoms among people living with HIV in Yangon, Myanmar. Methods In this cross-sectional study, data were collected from people living with HIV at three antiretroviral therapy clinics in 2017. Multiple logistic regression analyses were carried out to examine the associations between having self-help group membership and depressive symptoms. Three ART clinics were purposively selected based on the recommendation from the National AIDS Program in Myanmar. At these clinics, people living with HIV were recruited by a convenience sampling method. Results Among people living with HIV recruited in this study (n = 464), 201 (43.3%) were members of a self-help group. The membership was not associated with having depressive symptoms (adjusted odds ratio [AOR] 1.59, 95% confidence interval [CI] 0.98-2.59). Factors associated with having depressive symptoms were female (AOR 3.70, 95% CI 1.54-8.88) and lack of social support (AOR 0.97, 95% CI 0.96-0.98) among self-help group members, and female (AOR 3.47, 95% CI 1.70-7.09), lack of social support (AOR 0.98, 95% CI 0.97-0.99), and internalized stigma (AOR 1.28, 95% 1.08-1.53) among non-members. Conclusions This study did not find evidence on the association between membership in self-help groups and depressive symptoms among people living with HIV. Social support was a protective factor against depressive symptoms both self-help group members and non-members, although the level of social support was lower among members than non-members. The activities of self-help groups and care provided by the ART clinics should be strengthened to address mental health problems among people living with HIV in the study site.